Perencanaan Instalasi Pengolahan Lumpur IPA Parit Mayor Perumda Air Minum Tirta Khatulistiwa Kota Pontianak - Mulyanto, Rahmat; Winardi, Winardi; Apriani, Isna (Universitas Nusantara PGRI Kediri, 2023)
Government Regulation Number 112 of 2015 concerning the Drinking Water Supply System (SPAM), states that the drinking water supply system aims to provide services to fulfill people's rights to water which can be implemented by BUMN, BUMD, or other business entities. Perumda Air Drinking Tirta Khatulistiwa is a water provider located in Pontianak City, has a Parit Mayor Water Treatment Plant (IPA) to serve the people of East Pontianak using raw water from the Kapuas River. The type of residue that will be produced from IPA using river water will produce sludge as a residue from processing. Sludge residue will have an impact on the environment if disposed of directly, so a design is needed to design a sludge treatment unit. Treatment planning can use SNI 7510 of 2011 concerning procedures for planning sludge treatment in drinking water treatment plants with sludge drying tanks. Planning uses secondary data such as debit, alum dose, and raw water turbidity in 2020. The four tanks are designed with a required area of 345,902 m2, the available land area of 684.68 m2 is still sufficient for the construction of a sludge treatment plant. Therefore, a sludge treatment plan is carried out to treat residual sludge.